Intestinal formation of hypoxanthine and uric acid during endotoxemia - Schmidt, Heinfried; Weigand, Markus A.; Li, Chenghui; Schmidt, Werner; Martin, Eike; Bardenheuer, Hubert J. (Journal of surgical research, 1997)
The objective of this study was to examine the intestinal metabolism of high-energy purine compounds as sensitive indicators of tissue ischemia during endotoxemia. Arterial (art) and portal venous (PV) concentrations as well as the intestinal net concentration changes of adenosine (ADO), hypoxanthine (Hypo), and uric acid (UA) were measured at baseline and after 60 and 120 min in rats that were subjected to a 1-hr continuous infusion of endotoxin (1.5 mg/kg; group E), and in control animals (group C). Furthermore, the arterial (SaO2) and portal venous oxygen saturation (SPVO2) was determined at the same time points. Animals in both groups remained normotensive throughout the study period and no differences in mean arterial blood pressure were observed. In both groups, adenosine concentrations remained constant throughout the study and no changes in the net concentration difference (NCD) of adenosine between arterial and portal venous blood were observed [ADONCD; baseline: group E, −23 ± 46 nmole/L; group C, 17 ± 84 nmole/L; 120 min: group E, 14 ± 38 nmole/L; group C, 5 ± 40 nmole/L]. In contrast to control animals, hypoxanthine and uric acid concentrations increased in arterial and portal venous blood in endotoxemic rats after 120 min. This was accompanied with an increase in the intestinal net concentration differences of both hypoxanthine and uric acid, indicating the gut as the predominant source of these two compounds during endotoxemia [HypoNCD; baseline: group E, −36 ± 53 nmole/L; group C, −53 ± 185 nmole/L; 120 min: group E, 538 ± 211 nmole/L; group C, 99 ± 100 nmole/L] [UANCD; baseline: group E, 2.04 ± 1.62 μmole/L; group C, −0.04 ± 1.11 μmole/L; 120 min: group E, 9.58 ± 3.04 μmole/L; group C, 0.35 ± 1.34 μmole/L]. Furthermore, in endotoxemic rats the portal venous oxygen saturation decreased despite unaltered arterial oxygen saturation [SaO2; baseline: group E, 95.2 ± 0.9%; group C, 94.2 ± 0.9%; 120 min: group E, 95.4 ± 0.7%; group C, 96.4 ± 0.9%] [SPVO2; baseline: group E, 86.2 ± 3.1%; group C, 85.7 ± 1.4%; 120 min: group E, 69.1 ± 4.5%; group C, 82.3 ± 1.9%]. These results indicate the presence of tissue ischemia in the intestinal tract during early, normotensive endotoxemia. Furthermore, because of the direct toxic damage mediated by oxygen radicals that are generated during the production of uric acid, intestinal mucosal injury observed during endotoxemia may be related to an enhancement of the ATP-degradation pathway.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 04.01.2024